Flexible bronchoscopy as a valuable tool in the evaluation of persistent wheezing in children - KARADAĞ, BÜLENT TANER (ELSEVIER IRELAND LTD, 2009)
Background: Persistent wheezing is a common problem in early childhood and leads to a diagnostic dilemma, excessive investigations, drug administration and additional cost. Objective: To determine the efficacy and the safety of FOB in children with persistent wheezing despite bronchodilator and inhaled steroid therapy. Methods: Patients with persistent wheezing that lasted at least 6 weeks and did not respond to bronchodilator and inhaled steroid therapy and to whom flexible bronchoscopy was performed were included to the study. Results: Between 1997 and 2009; 113 patients were enrolled to the study. Sixty-three percent of the children were male. Median age was 14 months at presentation and median duration of symptoms was 5 months. Bronchoscopy revealed pathological findings in 48% of the patients. Thirty-eight patients had malacia disorders, 14 had foreign body aspiration and two had external compression of airways which were later diagnosed as vascular ring. Major and minor complications were not seen in 92% of the patients while transient hypoxia was seen in 6%, stridor in 1% and tachycardia in 1% of the patients. Conclusion: Flexible bronchoscopy provided rapid and definitive diagnosis for our patients with persistent wheezing without any major complications. This study is one of the largest studies concerning persistent wheezing. Early bronchoscopic evaluation can reduce cost by providing rapid and accurate diagnosis and preventing unnecessary investigations and drug administration. Flexible bronchoscopy is a safe procedure and should be considered in the evaluation of children with persistent wheezing. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Wheezing; Child; Tracheomalacia; Foreign body; Vascular ring; FOREIGN-BODY ASPIRATION; RESPIRATORY SYMPTOMS; BRONCHOMALACIA; TRACHEOMALACIA; DIAGNOSIS; DISEASE